A STUDY OF ATOMIC AND MAGNETIC STRUCTURE OF La2/3Pb1/3Mn1-xCoxO3 USING NEUTRON AND SYNCHROTRON DIFFRACTION METHODS - Loan, To Thanh; Bobrikov, I. V.; Nga, Tran Viet; Khai, Vu Van; Sinh, Nguyen Huy (Vietnam Journal of Science and Technology, 2015)
The samples with nominal composition of La2/3Pb1/3Mn1-xCoxO3 (x=0, 0.15, 0.20 and 0.25) were prepared by standard solid-state reaction method. Atomic and magnetic structures of the samples have been studied by neutron and synchrotron diffraction. The obtained result showed that, in wide temperature range (10-300 K) all investigated compounds are described by slightly distorted perovskite structure with rhombohedral symmetry (sp. gr. R-3c). The lattice parameters and bond distances Mn/Co–O are typical of rhombohedral manganites. Type of magnetic ordering doesn’t depend on doping level of Co: it is ferromagnetic at low temperature with average ordered value of magnetic moment in B-sites of about 3.5 μB at T < 20 K. In the compound with x = 0.15 there exist two crystal phases with the same symmetry but different stoichiometry. Only negligible changes of samples microstructure with composition were observed